2021
DOI: 10.1186/s40463-021-00507-z
|View full text |Cite
|
Sign up to set email alerts
|

Readability and quality assessment of internet-based patient education materials related to nasal septoplasty

Abstract: Background Given that nasal septoplasty is a common procedure in otolaryngology – head and neck surgery, the objective of this study was to evaluate the quality and readability of online patient education materials on septoplasty. Methods A Google search was performed using eight different search terms related to septoplasty. Six different tools were used to assess the readability of included patient education materials. These included the Flesch-K… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 34 publications
2
17
0
Order By: Relevance
“…In this study, the 22 sites with online education materials related to vocal cord leukoplakia were written at readability levels above those recommended by the AMA/NIH. These results are consistent with many other readability studies that have been published within otolaryngology 7,8,20,[28][29][30][31][32][33] and other specialties. [34][35][36][37][38][39][40][41][42][43] Similarly, PEMAT-P understandability and actionability scores were low.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In this study, the 22 sites with online education materials related to vocal cord leukoplakia were written at readability levels above those recommended by the AMA/NIH. These results are consistent with many other readability studies that have been published within otolaryngology 7,8,20,[28][29][30][31][32][33] and other specialties. [34][35][36][37][38][39][40][41][42][43] Similarly, PEMAT-P understandability and actionability scores were low.…”
Section: Discussionsupporting
confidence: 91%
“…8,9 These studies found a difference in DISCERN scores between patient-and physician-oriented websites in materials about in-office vocal fold injection 10 but not about swallowing difficulties. 9 One study 29 focused on nasal septoplasty and found that patient education materials originating from academic institutions had significantly higher scores in some DISCERN criteria than those originating from private clinics. Data from the current study support that there is no difference in understandability and actionability between sites about vocal cord leukoplakia directed at patients and those directed at physicians.…”
Section: Discussionmentioning
confidence: 99%
“…Besides improving the general health of the public and the understanding of pathology and treatment, improving the readability of PEMs may also indirectly serve an important role in decreasing the frequency with which malpractice litigation occurs [ 2 ]. Improving the readability of PEMs could be achieved by minimizing the use of complex words, decreasing the number of words per sentence and syllables per word, using numbering or bullet points, and writing in an active voice [ 11 ]. Subsequently, this will lead to a better understanding of the procedure context and outcomes by the patients which will then improve the relationship between them and their interventionalists.…”
Section: Discussionmentioning
confidence: 99%
“…However, if the cartilage is cut excessively, there is a risk of pollybeak deformity and other problems that require attention even in the C-shaped caudal septum. Patient education about complications as well as the expected benefits of surgery is important to improve patient satisfaction after surgery [ 14 ].…”
Section: Discussionmentioning
confidence: 99%